2=2(u-6)-2

Simple and best practice solution for 2=2(u-6)-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2=2(u-6)-2 equation:


Simplifying
2 = 2(u + -6) + -2

Reorder the terms:
2 = 2(-6 + u) + -2
2 = (-6 * 2 + u * 2) + -2
2 = (-12 + 2u) + -2

Reorder the terms:
2 = -12 + -2 + 2u

Combine like terms: -12 + -2 = -14
2 = -14 + 2u

Solving
2 = -14 + 2u

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-2u' to each side of the equation.
2 + -2u = -14 + 2u + -2u

Combine like terms: 2u + -2u = 0
2 + -2u = -14 + 0
2 + -2u = -14

Add '-2' to each side of the equation.
2 + -2 + -2u = -14 + -2

Combine like terms: 2 + -2 = 0
0 + -2u = -14 + -2
-2u = -14 + -2

Combine like terms: -14 + -2 = -16
-2u = -16

Divide each side by '-2'.
u = 8

Simplifying
u = 8

See similar equations:

| In+Inx^2=6 | | 4/k=2 | | p+77=13(4-p)+14p-5 | | 4/k=12 | | 6/u=2 | | 9/b=3 | | 9x-1=6x+3 | | 3(j+1)=9 | | d+87=11(1-d)+12d+76 | | 12-7x-4-x=11-8x+2x | | 10x^2+5x+1=10 | | 10x^2+5x+5=0 | | 6/g=3 | | 10x^2+5x+1=0 | | z=0.5y*x^2 | | 2x^34=50 | | -1+9=3b-7-2b | | 6x+2x+5=2x | | cos(x+5)=sin(3x+9) | | [x-3]=2x+5 | | pq^2+pq+p^2q= | | 6x^3-9x^2-36x+8=0 | | 5y^2+40y-75=0 | | .28x=2556.36 | | 4+6=446 | | 4n-24=56 | | 5x-55=-130 | | 5n+5-7n=15-12n+10n-10 | | 0.5(4x-8)=6x+10 | | 3G+24=9f | | -8x^2+12x+2=4x | | (x+1)(x+2)(x-2)=x^3+8 |

Equations solver categories